Copper-based oxygen carriers supported with alumina/lime for the chemical looping conversion of gaseous fuels - Haider, Syed Kumail; Erans Moreno, Maria; Donat, Felix; Duan, Lunbo; Scott, Stuart A.; Manovic, Vasilije; Anthony, Edward J. (Elsevier, 2017)
Copper (II) oxide in varying ratios was combined with either an alumina-based cement (Al300), or CaO derived from limestone as support material in a mechanical pelletiser. This production method was used to investigate its influence on possible mechanical and chemical improvements for oxygen carriers in chemical looping processes. These materials were tested in a lab-scale fluidised bed with CO or CH4 as a reducing gas at 950 °C. As expected, the oxygen carriers containing a greater ratio of support material exhibited an enhanced crushing strength. Oxygen carriers comprised of a 1:3 ratio of support material to active CuO exhibited increased crushing strength by a minimum of 280% compared to pure CuO pellets. All oxygen carriers exhibited a high CO conversion yield and were fully reducible from CuO to Cu. For the initial redox cycle, Al300-supported oxygen carriers showed the highest fuel and oxygen carrier conversion. The general trend observed was a decline in conversion with an increasing number of redox cycles. In the case of CaO-supported oxygen carriers, all but one of the oxygen carriers suffered agglomeration. The agglomeration was more severe in carriers with higher ratios of CuO. Oxygen carrier Cu25Al75 (75% wt. aluminate cement and 25% wt. CuO), which did not suffer from agglomeration, showed the highest attrition with a loss of approximately 8% of its initial mass over 25 redox cycles. The reducibility of the oxygen carriers was limited with CH4 in comparison to CO. CH4 conversion yielded 15-25% and 50% for Cu25Ca75 (25% wt. CuO and 75% wt. CaO) and Cu25Al75, respectively. Cu25Ca75 demonstrated improved conversion, whereas Cu25Al75 exhibited a trending decrease in conversion with increasing redox cycles.
Keywords: Chemical-looping; Oxygen carrier; Copper; Carbon capture